Disentangling the symptoms of schizophrenia: Network analysis in acute phase patients and in patients with predominant negative symptoms. Issue 1 (13th October 2022) - Demyttenaere, Koen; Leenaerts, Nicolas; Acsai, Károly; Sebe, Barbara; Laszlovszky, István; Barabássy, Ágota; Fonticoli, Laura; Szatmári, Balázs; Earley, Willie; Németh, György; Correll, Christoph U.
Abstract: Background: The Positive and Negative Syndrome Scale (PANSS) is widely used in schizophrenia and has been divided into distinct factors (5-factor models) and subfactors. Network analyses are newer in psychiatry and can help to better understand the relationships and interactions between the symptoms of a psychiatric disorder. The aim of this study was threefold: (a) to evaluate connections between schizophrenia symptoms in two populations of patients (patients in the acutely exacerbated phase of schizophrenia and patients with predominant negative symptoms [PNS]), (b) to test whether network analyses support the Mohr 5 factor model of the PANSS and the Kahn 2 factor model of negative symptoms, and finally (c) to identify the most central symptoms in the two populations. Methods: Using pooled baseline data from four cariprazine clinical trials in patients with acute exacerbation of schizophrenia ( n = 2193) and the cariprazine–risperidone study in patients with PNS ( n = 460), separate network analyses were performed. Network structures were estimated for all 30 items of the PANSS. Results: While negative symptoms in patients with an acute exacerbation of schizophrenia are correlated with other PANSS symptoms, these negative symptoms are not correlated with other PANSS symptoms in patients with PNS. The Mohr factors were partially reflected in the network analyses. The two most central symptoms (largest node strength) were delusions and uncooperativeness in acute phase patients and hostility and delusions in patients with PNS. Conclusions: This network analysis suggests that symptoms of schizophrenia are differently structured in acute and PNS patients. While in the former, negative symptoms are mainly secondary, in patients with PNS, they are mainly primary. Further, primary negative symptoms are better conceptualized as distinct negative symptom dimensions of the PANSS.